THE ECONOMIC REALITY IN THE FRAMEWORK OF ACCOUNTING INTERPRETATION - Natalya Adintsova; Elena Zhuravleva (Вестник Северо-Кавказского федерального университета)
The article is devoted to the issues of the debatable nature of the relationship of economic reality and its accounting interpretation in the system of accounting technology and presentation in reporting forms. Various approaches to understanding the essence of accounting reality from the point of view of accounting methodology construction are considered. In the process of transformation of views and the existing polarization of opinions on the compliance of the accounting interpretation of economic reality that has developed in the company is the professional judgment of the accountant as his mental program acts as a universal coordinator.